Technical Efficiency of Malaysian Furniture Manufacturing Industry: A Stochastic Frontier Analysis Approach - HAMDAN, HARTINI; Abdullah, Mohd Fahmy; Sieng, Lai Wei (International Journal of Supply Chain Management, 2019)
Global competition has been a major issue in furniture manufacturing industry. The wooden furniture is forced to improve their productivity in terms of price and design as it is becoming the sources of competitive advantage in the industry. Most of the previous studies do not take into account in assessing the technical inefficiency factors in order to improvise firm’s efficiency. The objective of this research is to measure the technical efficiency (TE) level in furniture manufacturing industry in Malaysia besides analyzing the technical inefficiency factors to improve the firm’s efficiency. Data in the firm levels which were obtained from Department of Statistics (DOS) and will be analyzed by using Stochastic Frontier Analysis (SFA). The study has used cross-sectional data of 710 firms acquired from DOS. The results of the study reveal that the average level of technical efficiency is high. The estimated result identifies the important determinants of technical inefficiency which are due to employee wage rates. The fundamental implication of this study is that furniture manufacturing firms need to boost motivation among employees and strengthen the network of the production market via wage increment.